Ribosomes binding to TAS transcripts buffer ta-siRNA biogenesis in Arabidopsis thaliana - Wang, Han; Wen, Qiming; Zhao, Minglei; He, Hualong; Cui, Jie; You, Chenjiang (Frontiers in Plant Science, 2025)
Small RNAs, including ta-siRNAs, play crucial roles in various processes in plants. Efforts have been made for decades to elucidate the biogenesis and function of ta-siRNAs. Though the key proteins involved in ta-siRNA biogenesis have been identified, the subcellular localization where ta-siRNAs are processed remains largely unexplored. Remarkably, non-coding TAS transcripts were reported to be bound by ribosomes, the machinery responsible for protein translation. Utilizing edited TAS genes in Arabidopsis, a combination of sRNA-seq, mRNA-seq, RIP-seq, and degradome-seq was employed to investigate the role of ribosomes in ta-siRNA biogenesis in this study. In the two-hit model, deletion of ribosome-binding regions resulted in a decrease in the abundance of intact TAS3 transcripts but did not significantly affect ta-siRNAs production or the efficiency of miRNA-guided cleavage. Conversely, the deletion of ribosome-binding regions led to a significant reduction in ta-siRNA abundance without affecting mRNA levels in the one-hit model. These findings indicate that in the two-hit model, ribosomes primarily stabilize TAS transcripts, while in the one-hit model, they suppress miRNA cleavage but facilitate subsequent processing. Collectively, this study proposes a model that ribosomes play distinct roles in the one-hit and two-hit models of ta-siRNA biogenesis, and provides a new angle to investigate the tangled connection between small RNAs, including miRNA and ta-siRNA, and translation.